Synthetic studies toward tricyclic cembranoids: a modular approach for the construction of the tricyclic framework of eunicin - Gurjar, MK; Nayak, S; Ramana, CV (Tetrahedron Letters, 2005)
The synthesis of a sugar derived allene and its intramolecular silver mediated etherification followed by ring closing metathesis has been explored for building the tricyclic framework of eunicin. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: Allene; Carbohydrate; cembranoid; eunicin; Ring closing metathesis

Relative reactivity of hydroxyl groups in inositol derivatives: role of metal ion chelation - Devaraj, Subramanian; Jagdhane, Rajendra C.; Shashidhar, Mysore S. (Carbohydrate Research, 2009)
O-Alkylation of myo-inositol derivatives containing more than one hydroxyl group via their alkali metal alkoxides (sodium or lithium) preferentially occurs at a hydroxyl group having a vicinal cis-oxygen atom. In general the observed selectivity is relatively higher for lithium alkoxides than for the corresponding sodium alkoxide. The observed regioselectivity is also dependent on other factors such as the solvent and reaction temperature. A perusal of the results presented in this article as well as those available in the literature suggests that chelation of metal ions by inositol derivatives plays a significant role in the observed regioselectivity. Steric factors associated with the axial or equatorial disposition of the reacting hydroxyl groups do not contribute much to the outcome of these O-alkylation reactions. These results could serve as guidelines in planning synthetic strategies involving other carbohydrates and their derivatives. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Carbohydrate; Chelation; Cyclitol; Inositol; Protecting group

Formal synthesis of valiolamine from myo-inositol - Jagdhane, Rajendra C.; Shashidhar, Mysore S. (Tetrahedron, 2011)
An efficient formal synthesis of racemic valiolamine starting from readily available myo-inositol is reported. In all the synthetic steps only one regioisomer is formed, which circumvents laborious purification of products. Regioselective benzylation of myo-inositol orthoformate, super-hydride mediated deoxygenation of a cyclitol derivative and stereoselective addition of dichloromethyllithium to an inosose are the key reactions in the synthesis. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Amino sugar; Carbohydrate; Cyclitol; Inositol; Natural product; Valiolamine

Engineering cell surface glycans with carbohydrate enantiomers to alter bacterial binding and adhesion - Gade, Madhuri; Chaudhary, Preeti Madhukar; Thulasiram, Hirekodathakallu V.; Kikkeri, Raghavendra (Chemistryselect, 2017)
Chirality of carbohydrate has critical functions in many biological processes. Changes in the configuration of even one sugar molecules may cause abnormal behavior or even inhibit specific processes. Herein, we have shown bioorthogonal conjugation of mannose enantiomers on HeLa cell surfaces induced a different rate of bacterial binding and cell adhesion.
Keywords: Bioorthogonal reaction; Carbohydrate; E. coli; Enantiomer; Surfaces functionalization

Palladium mediated selective cleavage of benzyl and allyl phosphates: a convenient non-hydrogenolytic method for the synthesis of phosphates and phospholipids. - Mart, Alson; Sarkar, Nitai N.; Shashidhar, Mysore S. (ChemistrySelect, 2022)
Palladium(II) hydroxide on carbon is a catalyst routinely used for the cleavage of O-benzyl groups by hydrogenolysis to obtain the corresponding parent organic compound. The work described in this article shows that allyl and benzyl phosphates, can be cleaved efficiently and selectively using palladium(II) hydroxide on carbon, under non-hydrogenolytic and neutral conditions, precluding the migration of acyl groups. The utility of these cleavage reactions for the synthesis of diacylglycerol and phosphatidic acid, containing unsaturation, is demonstrated. These methods have high potential for the synthesis of a variety of phosphates and natural phospholipids.
Keywords: Carbohydrate; Ether cleavage; Palladium; Phosphate; Phospholipid; Protecting group

Asymmetric synthesis of inositol derivatives - Patil, Nivedita T.; Sarkar, Nitai; Mysore, S. Shashidhar; Gonnade, Rajesh G. (Tetrahedron, 2024)
Both the enantiomers of racemic 4- O -tosyl-6- O -benzyl- myo -inositol-1,3,5-orthoformate ( 2 ) were isolated by preferential crystallization and used to synthesize several enantiomeric myo -inositol derivatives - natural ononitol, natural laminitol, precursors for myo -inositol phosphates and an oxabicyclo [2.2.1] heptane derivative. This work demonstrates the potential of the enantiomeric tosylates D2 and L2 to serve as versatile starting materials for the absolute asymmetric synthesis of inositol derivatives and other natural products from symmetric myo -inositol since no optically active molecular entity was required for the resolution of 2.
Keywords: Asymmetric synthesis; Carbohydrate; Cyclitol; Inositol; Natural product